Typology of English and German Coloronyms in Journalistic Discourse: Semantic Aspect - Oleksiienko, A. V.; Bespala, L. V.; Vovk, I. L.; Vysotska, Yu. S.; Олексієнко, Алла Валеріївна; Беспала, Лілія Володимирівна; Вовк, Ірина Леонідівна; Висоцька, Юлія Сергіївна (My University, 2022)
The article deals with a comprehensive study of English and German coloronyms in journalistic texts. The purpose of the study is to identify the semantic features of coloronyms and their functioning in English and German journalism. The procedure of studying English and German coloronyms in a journalistic text is implemented through linguistic research methods, namely: etymological method, analysis of dictionary definitions, semantic analysis and the context analysis. The results of the study are presented in the separation of associative fields and coloronyms in English and German, determining the frequency of use of basic coloronyms in English and German journalistic discourse. Coloronyms have been found to reflect changes in English-speaking and German-speaking society, as well as in the world as a whole. It was found that the units for the same color in English and German may have different connotations.
Oleksiienko A. V. - https://orcid.org/0000-0002-8868-1490; Bespala L. V. - https://orcid.org/0000-0002-6127-369X; Vovk I. L. - https://orcid.org/0000-0002-2998-765X; Vysotska Yu. S. - https://orcid.org/0000-0002-2976-1562.
Keywords: color; coloronym; connotative meaning; journalistic text; phraseological unit; narrative